2021
DOI: 10.3389/fnut.2021.751076
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Moringa Foods: A Food Chemistry Perspective

Abstract: The tree Moringa oleifera Lam. provides its leaves, pods, flowers and seeds for human nutrition. The chemical profile of all these Moringa products varies substantially, not only among the different parts of the plants used. Cultivating, processing as well as storage conditions chiefly determine the contents of nutrients and anti-nutritive constituents. Anti-nutrients, e.g., phytic acid or tannins, are present in notable amounts and may affect micronutrient bioavailability. Although Moringa oleifera products h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…In 2011, the Ministry of Health of the People's Republic of China issued a notice to consider M. oleifera l eaves as a new food resource. It has been demonstrated that M. oleifera has many biological functions such as anti-microbial, anti-oxidant, anti-inflammatory, anti-cancer, hepatoprotective, hypoglycemic, hypolipidemic, and other effects ( 30 32 ). However, the biological activities of M. oleifera polysaccharides (MOP) in regulating gut microbiota and alleviating obesity have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, the Ministry of Health of the People's Republic of China issued a notice to consider M. oleifera l eaves as a new food resource. It has been demonstrated that M. oleifera has many biological functions such as anti-microbial, anti-oxidant, anti-inflammatory, anti-cancer, hepatoprotective, hypoglycemic, hypolipidemic, and other effects ( 30 32 ). However, the biological activities of M. oleifera polysaccharides (MOP) in regulating gut microbiota and alleviating obesity have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Te pharmacological and medicinal aspects of these compounds are listed in Table 2. Te cultivation processes and storage of plant parts have a great infuence on the contents of these bioactive compounds which may afect its application and use [87].…”
Section: Bioactive Components and Their Medicinal Importance Of Morin...mentioning
confidence: 99%
“…It was found that eating 5–10 g of cookies made from M. oleifera for a period of 2 weeks increased the ability to concentrate in teenage males about the ages of 13 and 15 years 110 . Another experiment revealed that the seed extracts of M. oleifera had potential for use against amnesia in neuropharmacology.…”
Section: Biological Activities Associated With Moringamentioning
confidence: 99%
“…109 Enhancement of concentration It was found that eating 5-10 g of cookies made from M. oleifera for a period of 2 weeks increased the ability to concentrate in teenage males about the ages of 13 and 15 years. 110 Another experiment revealed that the seed extracts of M. oleifera had potential for use against amnesia in neuropharmacology. In addition, the study gathered that the same extracts from seeds can offer protection to mice from scopolamine-disrupted learning and recollection dysfunction.…”
Section: Against Urolithiasismentioning
confidence: 99%